EFEKTIVITAS CONJUGAL VISIT DI LEMBAGA PEMASYARAKATAN TERBUKA KELAS IIB NUSAKAMBANGAN - Sukardi, Sukardi -; Angkasa, Angkasa; Budiyono, Budiyono (MIH FH UNSOED, 2023)
The provision of conjugal visit facilities in prisons is one of the rights needed by prisoners as a maintenance and improvement of relationships with their legal partners, in addition to fulfilling their sexual desires and avoiding deviations of sexuality that prisoners are vulnerable to in prison. The effectiveness of the implementation of conjugal visits for prisoners in Nusakambangan Class IIB Open Correctional Institution can be said to be effective because prisoners who carry out the conjugal visit program feel the benefits in maintaining and maintaining the integrity and harmony of the household, so that prisoners who will soon be free feel more ready and confident to return to society. The obstacles faced by correctional officers in carrying out conjugal visits for prisoners in Nusakambangan Class IIB Open Correctional Institutions are from the aspect of legal substance, namely the implementation of the conjugal visit program at Nusakambangan Class IIB Open Correctional Institutions using assimilation rights and the right to receive family visits so that there is no implementing regulation that specifically regulates the conjugal visit program.